Political parties in Britain - Cole, Matthew, 1962-; Deighan, Helen (Politics study guides., 2012)
Looks at parties' organisation, policy, support and impact, from the major parties to the local. This introductory textbook examines the factors contributing to parties' fortunes and identities, and the causes of recent changes in both. Parties studied include: The main parties: Conservatives and Labour; The minor parties: the Liberal Democrats, the Scottish National Party, Plaid Cymru and the Greens; The peripheral parties: the BNP, UKIP, SSP and SLP; Local parties: Kidderminster Health and Hospital Concern, the Morecambe Bay Independents and Mebyon Kernow. Helpful student features include: A.